SPE Formation Damage Control Symposium 1988
DOI: 10.2118/17146-ms
|View full text |Cite
|
Sign up to set email alerts
|

A One-Dimensional Formation Damage Simulator for Damage Due to Fines Migration

Abstract: One of the major causes of formation damage is the movement and trapping of fine particles in pores. These fines may be generated in-situ by the interaction of injected fluids with the formation or they may be injected along with the fluids. A model is presented that simulates the permeability impairment caused by fines migration or injection in a radial geometry. The physical basis for the equations are the same as for a linear model that has been presented earlier. The equations are quite g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Ju and Dai [7] reported that one nanometerscale polysilicon material could change the wettability of porous surfaces of sandstone and consequently have effects on the flows of water and oil in oil formation when the suspension of the nanoparticles is injected into an oil reservoir. There are only few papers [8][9][10][11] dealing with mathematical modeling of fine particles migration in formation; however, none of which deals with the migration and adsorption of nanometer-scale materials in porous media.…”
Section: Introductionmentioning
confidence: 99%
“…Ju and Dai [7] reported that one nanometerscale polysilicon material could change the wettability of porous surfaces of sandstone and consequently have effects on the flows of water and oil in oil formation when the suspension of the nanoparticles is injected into an oil reservoir. There are only few papers [8][9][10][11] dealing with mathematical modeling of fine particles migration in formation; however, none of which deals with the migration and adsorption of nanometer-scale materials in porous media.…”
Section: Introductionmentioning
confidence: 99%
“…Vitthal et al (9) proposed a network model to predict permeability impairment owing to fines migration or fines injection. This model accounts for the details of the pore structure and can be used for any specified pore and particle size distribution.…”
Section: Literature Review Existing Modelsmentioning
confidence: 99%
“…The impact of suspended particles in water on the injectivity is very serious and this is an ordinary phenomenon. The degree and the velocity of plugging the pore system rely on the content of the suspended particles, particle size distribution, wettability character and the pore structure 6,7,8 . The suspended particles include products of corrosion, bacteria, emulsified oil and solid particles.…”
Section: Drilling and Completion Damage Evaluation By Well Testmentioning
confidence: 99%